New Orleans trip journal
Journal (1811 January 14-October 24) of a trip from the Ohio River to New Orleans, along the Mississippi River. Author unknown.
Collection material in English.
Keywords: Ship's papers -- 19th century; Louisiana -- Description and travel; Mississippi River -- Description and travel; New Orleans (La.) -- Description and travel; Ohio River -- Description and travel